Prevention of Postoperative Cognitive Dysfunction by Minocycline in Elderly Patients after Total Knee Arthroplasty: A Randomized, Double-blind, Placebo-controlled Clinical Trial. (13th December 2022) - Takazawa, Tomonori; Horiuchi, Tatsuo; Orihara, Masaki; Nagumo, Kazuhiro; Tomioka, Akihiro; Ideno, Yuki; Hayashi, Kunihiko; Yashima, Hideaki; Araki, Takuya; Hatayama, Kazuhisa; Terauchi, Masanori; Ikeda, Yoshio; et al.
Abstract : Background: There are no effective pharmacologic interventions for preventing postoperative cognitive dysfunction in daily practice. Since the antibiotic minocycline is known to suppress postoperative neuroinflammation, this study hypothesized and investigated whether minocycline might have a preventive effect on postoperative cognitive dysfunction after noncardiac surgery. Methods: This study included patients aged more than 60 yr undergoing total knee arthroplasty under general anesthesia. They were randomly assigned to minocycline and placebo groups, to orally receive 100 mg of minocycline or placebo twice daily from the day before surgery until the seventh day after surgery. Cognitive function was evaluated before surgery, and 1 week and 3 months after surgery, using a battery of four cognitive function tests, including Visual Verbal Learning Test, Trail Making Test, Stroop Color and Word Test, and Letter–Digit Coding Task. Additionally, 30 healthy volunteers were subjected to the same tests as the patients to examine the learning effect of repeated tests. The occurrence of postoperative cognitive dysfunction was judged from the results of the neurocognitive test battery, with consideration of the learning effect. The secondary endpoints were the effects of minocycline on postoperative delirium and postoperative pain. Results: A total of 100 patients were randomized to the minocycline group, and 102 were randomized to the placebo group. The average age of patients was 75 yr. Evaluation showed no significant difference in the incidence of postoperative cognitive dysfunction between the minocycline and placebo groups at both 1 week (8 of 90 [8.9%] vs. 4 of 95 [4.2%]; odds ratio, 2.22 [95% CI, 0.64 to 7.65]; P = 0.240) and 3 months (15.3 of 90 [17.0%] vs. 15.3 of 95 [16.1%]; odds ratio, 1.07 [95% CI, 0.49 to 2.32]; P = 0.889) postoperatively. Missing data 3 months after surgery were corrected by the multiple imputation method. There were no differences between the two groups in postoperative delirium and postoperative pain. Conclusions: Minocycline is likely to have no preventive effect on postoperative cognitive dysfunction. Abstract : A prospective, double-blind, randomized controlled trial compared the effects of the anti-inflammatory drug minocycline versus placebo on the incidence of postoperative cognitive dysfunction after total knee arthroplasty in two centers in Japan. There were no differences in the incidence of postoperative cognitive dysfunction between minocycline and placebo control groups at 1 week or 3 months after surgery and anesthesia.